A methodology for estimating detectable change in water quality due to prescribed fire in northern Colorado - Lange, Robert William, author (Colorado State University. Libraries, 2001)
Increases in nutrients and metals in receiving waters have been documented after wildfire. However, water quality impacts from prescribed fire are not well known. This research investigated the design of a post-fire water quality monitoring program using a pre-fire dataset to detect water quality changes from prescribed fire. Since water quality changes due to land use practices are often difficult to detect due to high natural variability, a paired watershed approach was implemented. Two small watersheds were selected in the Cache la Poudre watershed in Northern Colorado and monitored for one year, resulting in 14 pre-fire water quality samples. A single station and paired approach, which consider statistical power are presented and the minimum detectable change is calculated for a range of post-fire sample sizes. Samples from the Bobcat Fire in the Big Thompson Watershed near Drake, Colorado are used to evaluate the results. These results show that with 16 post-fire samples a change of less than 1% of the difference between pre-firewater quality samples and samples from the Bobcat Fire can be detected for most parameters with a statistical power of 80%. The paired watershed approach is shown to reduce the minimum detectable change by half for parameters that are correlated between the two watersheds.
Keywords: Water quality -- Colorado; Prescribed burning -- Colorado